2007
DOI: 10.1253/circj.71.973
|View full text |Cite
|
Sign up to set email alerts
|

Beta-, Not Alpha-Adrenergic Stimulation Enhances Conduction Velocity in Cultures of Neonatal Cardiomyocytes

Abstract: n the mature circulatory system, -adrenergic stimulation predominantly affects vessel diameter whereas 1-adrenergic stimulation determines the adaptation of heart rate and contractility to changing demands. In the immature stages of heart development, postnatal maturation coincides with in-growth of sympathetic neurons, elevated levels of released catecholamines and enhanced expression of -adrenoreceptors. 1 Shortly after birth, hyperplasia of the cardiomyocytes ceases and is followed by hypertrophic growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
11
2
Order By: Relevance
“…These results coincided with those of De Boer et al [18] . Namely, betaadrenergic stimulation, and not alpha-adrenergic stimulation, enhances conduction velocity in cultures of neonatal cardiac myocytes.…”
Section: Discussionsupporting
confidence: 93%
“…These results coincided with those of De Boer et al [18] . Namely, betaadrenergic stimulation, and not alpha-adrenergic stimulation, enhances conduction velocity in cultures of neonatal cardiac myocytes.…”
Section: Discussionsupporting
confidence: 93%
“…21 Long-term (>2 h) stimulation by the β-adrenergic agonist isoproterenol results in an increase in the expression of Ca v 1.2 as well as auxiliary subunits α 2 δ and β 2 a in myocytes cultured in serum-containing media. [22][23][24] PKA stimulation increases the mRNA levels of Ca v 1.2 and β 2 a in myocytes, an effect that saturated after 8 h. 22,23 Consistent with these findings, we showed that at 7 h of treatment, 8Br-cAMP increased and H89 reduced the HVA calcium current component, suggesting that the channels may be regulated through PKA-dependent mechanisms. Unexpectedly, we observed that long-term treatment with H89 persistently increased both HVA and LVA current densities.…”
Section: O N O T D I S T R I B U T Esupporting
confidence: 81%
“…[22][23][24] PKA phosphorylation of the VDCCs also regulates channel activity. Upon β-adrenergic stimulation, PKA activation increases myocardial contractility (positive inotropy) via upregulation of the HVA Ca v 1.2 channel activity.…”
Section: Differential Regulation Of Low and High Voltage-activated Camentioning
confidence: 99%
“…The effects of sympathetic excitation include APD shortening via modulation of the slow inward rectifying potassium channel (IK S ), increased repolarization heterogeneity, increased intracellular calcium, and increased afterdepolarizations (5), among other effects. The sodium channel NaV1.4 (encoded by SCN5A) is known to be upregulated and modulated by ␤-adrenergic stimulation (13,31). However, this is on a longer time scale and unlikely to have played a role on the short-term effects of SGS studied here.…”
Section: Discussionmentioning
confidence: 82%
“…CV anisotropy ϭ CVL/CVT. Impact of ␤-adrenergic receptor activation on GJ conductance from de Boer et al (13). estimate local APD has limitations.…”
Section: Discussionmentioning
confidence: 99%